Treatment target achievement after myocardial infarction and ischemic stroke: cardiovascular risk factors, medication use and lifestyle – The Tromsø Study 2015-2016. Secondary prevention in myocardial infarction and stroke - Hopstock, Laila Arnesdatter; Morseth, Bente; Cook, Sarah; Eggen, Anne Elise; Grimsgaard, Sameline; Lundblad, Marie Wasmuth; Løchen, Maja-Lisa; Mathiesen, Ellisiv B.; Nilsen, Amalie; Njølstad, Inger (European Journal of Preventive Cardiology, 2021)
Aims - To investigate European guideline treatment target achievement in cardiovascular risk factors, medication use, and lifestyle, after myocardial infarction (MI) or ischaemic stroke, in women and men living in Norway. Methods and results - In the population-based Tromsø Study 2015–16 (attendance 65%), 904 participants had previous validated MI and/or stroke. Cross-sectionally, we investigated target achievement for blood pressure (<140/90 mmHg, <130/80 mmHg if diabetes), LDL cholesterol (<1.8 mmol/L), HbA1c (<7.0% if diabetes), overweight (body mass index (BMI) <25 kg/m2, waist circumference women <80 cm, men <94 cm), smoking (non-smoking), physical activity (self-reported >sedentary, accelerometer-measured moderate-to-vigorous ≥150 min/week), diet (intake of fruits ≥200 g/day, vegetables ≥200 g/day, fish ≥200 g/week, saturated fat <10E%, fibre ≥30 g/day, alcohol women ≤10 g/day, men ≤20 g/day), and medication use (antihypertensives, lipid-lowering drugs, antithrombotics, and antidiabetics), using regression models. Proportion of target achievement was for blood pressure 55.2%, LDL cholesterol 9.0%, HbA1c 42.5%, BMI 21.1%, waist circumference 15.7%, non-smoking 86.7%, self-reported physical activity 79%, objectively measured physical activity 11.8%, intake of fruit 64.4%, vegetables 40.7%, fish 96.7%, saturated fat 24.3%, fibre 29.9%, and alcohol 78.5%, use of antidiabetics 83.6%, lipid-lowering drugs 81.0%, antihypertensives 75.9%, and antithrombotics 74.6%. Only 0.7% achieved all cardiovascular risk factor targets combined. Largely, there was little difference between the sexes, and in characteristics, medication use, and lifestyle among target achievers compared to non-achievers. Conclusion - Secondary prevention of cardiovascular disease was suboptimal. A negligible proportion achieved the treatment target for all risk factors. Improvement in follow-up care and treatment after MI and stroke is needed.